Upflow anaerobic sludge blanket reactor (UASB) performance through sludge age load and kinetic coefficients - Pérez, Jhonny; Aldana, Gerardo; Cárdenas, Carmen (Rev. Téc. Fac. Ing. Univ. Zulia, 1970)
Upflow anaerobic sludge blanket reactor (UASB) performance is influenced by change in the hydraulic and organic load. Aim of this study was to evaluate the performance for a 4.14L reactor controlling temperature (30 Ó 1°C) with a jacket circulation and a thermostat bath. Sludge age and kinetic coefficients were calculated. 500 mg/L of glucose as volumetric organic load were tested for different loading from 0,50 to 3.0 kgCOD/m3d kgCOD/m3d. Theoretical hydraulic retention time assayed from 24 to 4 hours, keeping a constant flow rate with a peristaltic pump. Sludge age recommended was 165 days and it was found enough to achieve a COD reduction by 86.87%. Rate constants found were: decay coefficient endogenous (Kd) = 0.0023 d”“1, yield coefficient cell (Y) = 0.0767 KgSSV/KgDQOr, maximum rate of substrate utilization per unit of microorganisms, (k) = 0.2578 mgDQO/mgSSV.d, substrate saturation constant (Ks) = 214 mg/L and maximum specific growth rate (Î¼max) = 0.0198 d”“1. Equation found by linear regression was able to predict the an operation of the reactor with a standard error of 1.882% in terms of CODÂ´s efficiency. Rate coefficients proposed by the process was developed successfully.